ANALISIS ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) DAN PERSON ORGANIZATION FIT(PO-FIT) TERHADAP KINERJA KARYAWAN BAGIAN NON MEDIS RUMAH SAKIT ISLAM SITI KHODIJAH PALEMBANG - Hadiwijaya, Hendra (Universitas Muhammadiyah Palembang, 2017)
Purpose - The aim of this research is to know and analyze the magnitude of influence of organization citizenship behavior and person organization fit on the performance of non-medical employees Hospital Islam Siti Khodijah Palembang either partially or simultaneously.Â Design/methodology - This research uses a questionnaire and the population of this research is 245. The data is analyzed with Multiple Linear regression using computer statistical package. Findings â€“ The author finds that the Organization Citizenship Behavior and Person Organization Fit had significant partial and simultaneous impact on the Performance of Employees and Person Organization Fit have dominant influence to Employee Performance to Non-medical Participants of Islamic Hospital Siti Khodijah Palembang.